Combined 2-deoxy glucose and metformin improves therapeutic efficacy of sodium-iodide symporter-mediated targeted radioiodine therapy in breast cancer cells - Chatterjee, Sushmita (Breast Cancer (Dove Med Press), 2015)
Radiosensitization using either metformin or 2-deoxy-d-glucose (2-DG) in various cancer cells has been reported. The present study reveals novel information on combining these drugs to enhance radiosensitization effect in breast cancer (BC) cells. Responses to low-dose Cobalt60 radiation, as well as a newly emerged radioiodine therapy target for BC, that is, sodium-iodide symporter (NIS or SLC5A5) protein, are tested. As therapeutic potential of NIS in BC is often limited due to low uptake and fast efflux rate of iodine, the scope of these two radiosensitizers to further improve NIS-mediated (131)I therapeutic efficacy is explored. Two BC cell lines, MCF-7, and MDA MB231 are tested to optimize minimal drug doses required for radiosensitization. A combination of 2 mM metformin and 20 mM 2-DG with 2 grey (Gy) Cobalt60 radiation shows significant radiosensitization effect (P=0.0002). In cells treated with the combination therapy, increased γH2A.X foci formation was noted. Further, MCF-7 BC cells overexpressing NIS (MCF-7 NIS) was established, and using the optimized drug concentrations, significant radiosensitization (P=0.0019) by 50 μ Ci (131)I usage was found to be the case as well. Apoptosis data corroborates with the result of clonogenic assay showing significant increase in apoptotic population upon dual drug-mediated radiosensitization. In case of metformin treatment, lowered adenosine triphosphate (ATP) content of the cell has been observed. The encouraging radiosensitization effect observed using combined 2-DG and metformin may aid in reducing Cobalt60 radiation exposure or for targeted radioiodine therapy in BC cells with NIS expression. This study indicates high potential of this drug combination in sensitizing BC cells for NIS-mediated-targeted radioiodine therapy, which otherwise may have lacked efficacy.